15 hedendaagse Gentse Kunstenaars. - Stedelijk Museum De Lakenhal, Leiden; Eeckhout, Paul; van Kinschot, F.H. (Leiden : Stedelijk Museum De Lakenhal, 1953)
Burssens, Jan ; De Keyser, Marie ; Dupuis, Maurice ; Hermans, Gerard ; Mees, Jozef ; Morel, Philippe ; Mulder, Jan ; van der Eecken, Victor ; Verdegem, Jos ; Vlerick, Pierre ; Wauters, Alex ; Cantré, Jozef ; Coolens, Bert (Berten, Robert) ; Poetou, Emiel ; Verbanck, Geo
Nederlands
15 hedendaagse Gentse Kunstenaars, Stedelijk Museum De Lakenhal, Leiden, 7 Nov. - 7 Dec. 1953
kunstcatalogus
Keywords: jaren 50; Gent